Penerapan Metode Simple Additivie Weighting Untuk Mengefektifkan Penilaian Kinerja Karyawan - Neni Mulyani; Jeperson Hutahaean (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
In this study, the application of the Simple Additive Weighting (SAW) method is needed to generate preference values for 16 employee data which is used as an alternative employee performance appraisal. The application of the SAW method in this case also aims to improve the results of decisions made by managers. So that in one period of performance appraisal of employees at the end of the year the manager can make decisions on employees who have very good performance (0.80 – 1.00) to employees who have poor performance. The results of the preference value from the calculation using the SAW method will be made in the form of an assessment range, so that based on the value of the range the manager can provide an employee performance assessment.